2022
DOI: 10.1016/j.ejvs.2021.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Update of the European Society for Vascular Surgery (ESVS) 2020 Clinical Practice Guidelines on the Management of Acute Limb Ischaemia in Light of the COVID-19 Pandemic, Based on a Scoping Review of the Literature

Abstract: Objectives Perform a scoping review how COVID-19 patients are affected by acute limb ischaemia (ALI). Evaluate the recommendations of the 2020 ESVS ALI Guidelines for these patients. Methods Research questions were defined, followed by a systematic literature search according to the PRISMA guideline. Abstracts and unpublished literature were not included. The definition of ALI accords to ESVS guidelines. Results Most identified papers were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 68 publications
0
27
0
1
Order By: Relevance
“…Interestingly, the number of interventions for ALI was not significantly altered in the present study. Since the effect of SARS-CoV-2 on the prevalence of arterial thrombosis is still uncertain ( 14 ), our findings might help comprehend this along with data from future publications.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, the number of interventions for ALI was not significantly altered in the present study. Since the effect of SARS-CoV-2 on the prevalence of arterial thrombosis is still uncertain ( 14 ), our findings might help comprehend this along with data from future publications.…”
Section: Discussionmentioning
confidence: 84%
“…The recommendations regarding the anticoagulation treatment in patients with ALI and SARS-CoV-2 infection are not well established yet. In a study on 20 patients who underwent revascularization, the usage of systemic heparin was associated with increased survival [38,39]. In this study, all the patients received low molecular weight heparin after revascularization, and none of them required reintervention, which leads to the possibility that heparinization prevents recurrent thrombosis and improves the rate of survival and limb salvage.…”
Section: Discussionmentioning
confidence: 90%
“…An update of the Guidelines of the European Society for Vascular Surgery (ESVS) was made regarding the management of acute ischemia related to Sars-Cov2/COVID-19 and recommends the realization of an angio-CT including the aorta in its totality and the iliac arteries. 23 Avila at al. reviewed 95 studies of the literature and reported that the lower limb arteries and the abdominal or thoracic aorta were the most frequent localizations of acute thrombotic events of arterial origin.…”
Section: Discussionmentioning
confidence: 99%